Factors influencing development of dairy cattle farming in Malaysia - Faghiri, Hamed (2019)
The Malaysian dairy cattle industry does not produce enough quantity of dairy products to satisfy domestic market needs. As a result, Malaysia is one of the highest milk importing countries in the world. The objectives of the thesis are to identify the competitiveness of the factors influencing the dairy cattle industry, investigate and focus into the most important factors affecting the dairy cattle industry development, and determine the most appropriate dairy farm model in terms of initial investment and herd size for the nation. The population of this study covers Peninsular Malaysia’s dairy cattle industry. The exploratory mix method is applied to initially identify the competitiveness level of factors and later to focus on the most important factors affecting the industry development in Malaysia. The qualitative approach is used to identify the competitiveness of the factors influencing the dairy cattle industry. The sample of twelve participants were interviewed and the data are collected from semi-structured open-ended interviews. This study integrates the theory-driven and data-driven codes using Nvivo 10 software. The results show that most of the factors have low competitiveness level and the issues have spread to all aspects of the industry such as factor condition; related and supporting industries; company’s structure; rivalry and organization; government’s role; accessibility; and costs. There are only a few factors such as demand, natural resources (water), infrastructure (utilities and logistics) have a high and moderate level of competitiveness. Therefore, the contributions of many relevant stakeholders are very vital for any future improvement and development of this industry.The quantitative is implemented to investigate and focus on the most important factors affecting the dairy cattle industry in Malaysia. In this part, an original research instrument has been developed. The Content Validity Index (CVI) method is applied in the pretesting and the reliability test (Cronbach’s alpha technique) is used in the pilot test. The Structural Equation Modelling (SEM) is implemented to analyze the data by using the Smart-PLS 3 software. The findings demonstrate that the factors such as adequate land allocation for dairy farming and animal feed plantation, climate condition, logistic costs, animal feed price and accessibility, poor cow breed, lack of well trained and experienced labors, lack of knowledge on dairy farming, government policies, and the inappropriate environment of the industry are among the most important factors affecting Malaysian dairy cattle industry growth. The results of this part provide a roadmap for the dairy cattle industry stakeholders for their future development plan. Finally, Cost and Benefit Analysis (CBA) is applied on 4 different dairy cattle farms with 100, 250, 500 and 1,000 milking dairy cows’ capacity and 8, 20, 40 and 80 ha animal feed ranching. The outcomes show that the most ideal farm size is at least 1,000 heads milking dairy cows for Malaysia because it generates lower average costs and more income. However, bigger size farms need higher investment. Our study indicates that the most viable farm size is 500 cows because it is feasible and efficient enough at a lower investment rate. Additionally, farm with 250 cows is advisable just for the start with the aim to expand in the future. Finally, farms with smaller herds of less than 250 cows are not recommended because of the low income and high risk. In conclusion, this study identified the competitiveness and level of importance of the factors affecting dairy cattle industry in Malaysia besides the most viable dairy farm size for Malaysia. These findings provide benefits to many dairy cattle industry stakeholders such as farmers, policymakers and researchers. Farmers can use these results to improve their current farm situation or in their future farm design. This information acts as a comprehensive roadmap for the policymakers for their future dairy cattle development plan. Finally, determining the appropriate solution for each of the explored critical factors in this industry can be a topic for future research.